Temperature effect on pseudomonas aeruginosa growth and its presence on corrosion of steel wire rope - Hasim, N. (Trans Tech Publications Ltd, 2020)
Bacterial can initiate, accelerate, and/or inhibit corrosion processes through a number of different ways, including modification of the localized environment at the metal/solution interface by causing pitting attack. In this work, the effect of temperature on bacteria (P.Aeruginosa sp) growth will be investigated the nature of bacteria before further investigated its corrosion effect on steel wire rope. It is found that the bacteria grew actively at 30 ÂºC. The pH value was also changed from 7 to 8. The corrosion rate with the presence of bacteria has been found increased from 9.95 x 10-7 mdy to 4.884 x 10-5 mdy. While corrosion pitting is found directly proportional to the bacterial activity. Â© 2020 Trans Tech Publications Ltd, Switzerland.